2015
DOI: 10.3892/ijmm.2015.2126
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 inhibits the invasion and migration of colon cancer cells by targeting the PI3K/Akt/mTOR signaling pathway

Abstract: Abstract. Colon cancer is one of the most common and lethal malignancies worldwide. Despite major advances in the treatment of colon cancer, the prognosis remains very poor. Thus, novel and effective therapies for colon cancer are urgently needed. In the present study, the expression status of miR-218 and the role of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway were investigated in colon cancer samples. Firstly, we observed that miR-218 expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 52 publications
4
44
0
2
Order By: Relevance
“…Integrin β-1 receptors are associated with increased invasiveness in many cancers (3739) and induce cell proliferation and survival (40). PI3K/Akt signaling, the most frequently altered pathway in many cancers (41,42), was inhibited by miR-6126 and was associated with integrin β-1 protein inhibition. Activation of PI3K/Akt signals has been known to play major roles in migration (43), invasion (44), angiogenesis (45), and proliferation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β-1 receptors are associated with increased invasiveness in many cancers (3739) and induce cell proliferation and survival (40). PI3K/Akt signaling, the most frequently altered pathway in many cancers (41,42), was inhibited by miR-6126 and was associated with integrin β-1 protein inhibition. Activation of PI3K/Akt signals has been known to play major roles in migration (43), invasion (44), angiogenesis (45), and proliferation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SEMA3F prevented metastasis of colorectal cancer by PI3K/Akt-dependent downregulation of the ASCL2/CXCR4 Axis [49]. Ginsenoside Rh2 inhibited metastasis of glioblastoma multiforme through Akt-regulated MMP13 [50]. MiR-218 inhibited the invasion and migration of colon cancer cells by targeting the PI3K/Akt/mTOR signaling pathway [51].…”
Section: Figmentioning
confidence: 99%
“…The association between miRNAs and tumour chemo-sensitivity has recently attracted increased attention [8]. Some research has shown that miR-218 acts as a tumour-suppressing miRNA in many cancers, including glioma, cervical cancer and colon cancer [11-13]. Our previous study showed that miR-218 expression was down-regulated in clinical bladder cancer tissues and inhibited the proliferation, migration and invasion of bladder cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%